The Automatic Emotion Regulation of Children Aged 8–12: An ERP Study - Liu, Fang; Gao, Chao; Gao, Heming; Liu, Wen (Frontiers in Behavioral Neuroscience, 2022)
Emotion regulation in childhood and adolescence is related to their social development. Better emotion regulation is associated with great individual academic performance and mental health. However, compared with the research on emotion regulation strategies, children's automatic emotion regulation has been less investigated. Using event-related potential (ERP) technology, this study adopts the cued-emotion Go/Nogo paradigm to investigate the processing characteristics of automatic emotion regulation in children aged 8–12 years. The current study selected 34 younger group (16 boys, 18 girls, M ± SD = 8.91 ± 0.75), and 31 older group (18 boys, 13 girls, M ± SD =11.26 ± 0.45). The results showed that, for Nogo trials, The amplitude of N2 and P3 evoked by emotional faces were significantly larger than those evoked by neutral faces, reflecting the cognitive conflict experienced and the process of children's automatic response inhibition to emotional stimuli, respectively. However, no significant difference in N2 and P3 amplitude were found in Go trials, which may indicate that children aged 8–12 showed similar top-down control and similar motivated attention in this experiment, respectively. Further analysis found that the negative affect of temperament was significantly positively correlated with Nogo-P3 induced by neutral pictures (r = 0.37, p < .001), and preadolescents’ social anxiety was significantly positively correlated with Nogo-P3 followed by neutral pictures (r = 0.31, p < .01). These findings can provide inspiration and empirical support for the promotion and intervention of emotion regulation in children and adolescents.